A systematic review of syphilis serological treatment outcomes in HIV-infected and HIV-uninfected persons: rethinking the significance of serological non-responsiveness and the serofast state after therapy. Issue 1 (December 2015) - Seña, Arlene; Zhang, Xiao-Hui; Li, Trudy; Zheng, He-Ping; Yang, Bin; Yang, Li-Gang; Salazar, Juan; Cohen, Myron; Moody, M.; Radolf, Justin; Tucker, Joseph
Abstract Background Syphilis remains a global public health threat and can lead to severe complications. In addition to resolution of clinical manifestations, a reduction in nontreponemal antibody titers after treatment is regarded as "proof of cure." However, some patients manifest < 4-fold decline ("serological non-response") or persistently positive nontreponemal titers despite an appropriate decline ("serofast") that may represent treatment failure, reinfection, or a benign immune response. To delineate these treatment phenomena, we conducted a systematic review of the literature regarding serological outcomes and associated factors among HIV-infected and -uninfected subjects. Methods Six databases (PubMed, Embase, CINAHL, Web of Science, Scopus, and BIOSIS) were searched with no date restrictions. Relevant articles that evaluated serological treatment responses and correlates of serological cure (≥ four-fold decline in nontreponemal titers) were included. Results We identified 1693 reports in the literature, of which 20 studies met selection criteria. The median proportion of patients who had serological non-response was 12.1 % overall (interquartile range, 4.9–25.6), but varied depending on the time points after therapy. The serofast proportion could only be estimated from 2 studies, which ranged from 35.2–44.4 %. Serological cure was primarily associated with younger age, higher baseline nontreponemal titers, and earlier syphilis stage. The relationship between serological cure and HIV status was inconsistent; among HIV-infected patients, CD4 count and HIV viral load was not associated with serological cure. Conclusions Serological non-response and the serofast state are common syphilis treatment outcomes, highlighting the importance of determining the immunological and clinical significance of persistent nontreponemal antibody titers after therapy.